Analisis diksi dan gaya bahasa dalam lagu Sewu Kutha karya Didi Kempot: kajian stilistika - Prasanti, Alfina Diah Ayu; Sulanjari, Bambang (Kaloka Jurnal Pendidikan Bahasa dan Sastra Daerah, 2023)
This study discusses the use of diction, language style, imagery and figure of speech in the lyrics of the campursari song entitled Sewu Kutha by Didi Kempot. The theory used is a stylistic study. This study aims to: (1) describe the diction (2) describe the imagery (3) describe the figure of speech or language style contained in the lyrics of the campursari song entitled Sewu Kutha by Didi Kempot. The method used in this research is descriptive analysis. The data collection technique used is reading and note-taking technique and data analysis technique using descriptive analysis technique which includes description, classification and analysis. The results of this study are in the lyrics of the campursari song entitled Sewu Kutha created by Didi Kempot using denotative diction, connotative diction, tactile imagery, visual imagery, auditory imagery, comparative language style, affirmation style.